The learning of the english spelling patterns in a deductive way is of great help to spanish learners of english - Reyes Santamaría, Franklin Alvaro
The learning of English spelling patterns related to the pronunciation of single vowels and the clusters of vowels within monosyllabic words, in a deductive way in the teaching-learning process of English is of great help to adult second language learners of English, although vowels’ pronunciation problems may arise due to irregularities in each spelling pattern and the nonexistence of equivalent vowel sounds in the English learners’ mother tongue and its spelling pattern system. Linguistics shows us that the man has devised a complex set of symbols to represent the sounds of speech in a written way, and every language has its own idiosyncrasy; i.e., particular ways of combining symbols to build up words or ideas to convey human thoughts. “English employs an alphabetic system of writing (spelling) in which symbols are used to represent individual consonants and vowels rather than syllables or words. The set of conventions for representing language in a written form is called an orthography” (O’Grady, et al; 1989: 376). If both assertions are true, then this implies that English language possesses its own specific spelling patterns for representing vowel and consonant sounds within English words.